2022
DOI: 10.1002/acp.3901
|View full text |Cite
|
Sign up to set email alerts
|

Decision making and heart rate variability: A systematic review

Abstract: Heart rate variability (HRV) reflects the balance of the autonomic nervous system and is associated with cognitive functions. However, its relationship with the process related to making a decision is unclear. This systematic review aims to analyze the relationship between HRV and decision-making. A qualitative analysis was conducted according to the PRISMA-Statement. Fifteen studies were included, with a total of 1051 healthy participants. Our results show an association between higher vagally mediated HRV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…However, a placebo [ 50 ] also generates a similar response. The findings suggest that placebo analgesia, induced administering a placebo, can increase HRV and induce pain relief [ 37 , 50 ], consistent with the Neurovisceral Integration Model [ 19 , 25 ]. Furthermore, autonomic responses to the same painful stimulation can differ depending on the affective states [ 32 ] or the empathetic or unempathetic context [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, a placebo [ 50 ] also generates a similar response. The findings suggest that placebo analgesia, induced administering a placebo, can increase HRV and induce pain relief [ 37 , 50 ], consistent with the Neurovisceral Integration Model [ 19 , 25 ]. Furthermore, autonomic responses to the same painful stimulation can differ depending on the affective states [ 32 ] or the empathetic or unempathetic context [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 74%
“…The Vagal Tank Theory [ 100 ], relying on the Neurovisceral Integration Model [ 17 ], highlights the role of the vagus nerve in the control of cardiac activity and in goal-directed behavior, as well as in the individual self-regulation ability [ 100 ]. The Neurovisceral Integration Model [ 17 , 19 ] assumes that the goal-directed behavior and the self-regulation ability of an organism are structurally and functionally supported by the Central Autonomic Network [ 18 ], a complex network of brain structures whose primary output is the cardiac vagal control expressed by HRV. Accordingly, our study confirms a relationship between the autonomic nervous system indexed by HRV and the pain response to nociceptive stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to stimulate for only 10 min, according to studies that found HR changes soon after taVNS onset ( Keute et al, 2019 ; Sclocco et al, 2019 ; Sharon, Fahoum & Nir, 2021 ). Therefore, recordings of less than 10 min provide reliable HRV indices ( Forte, Favieri & Casagrande, 2019 ; Forte et al, 2021 ; Forte et al, 2022a ; Forte et al, 2022b ; Melo et al, 2018 ; Munoz et al, 2015 ; Nussinovitch et al, 2012 ; Thong et al, 2003 ; Voss et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outliers (less than 1% of the data) were removed. According to previous studies ( Forte et al, 2021 ; Forte et al, 2022a ), HRV data were log-transformed for approximately following normal distribution.…”
Section: Methodsmentioning
confidence: 99%